ANALISIS KOLABORASI PENTA-HELIX DALAM IMPLEMENTASI SUSTAINABLE DEVELOPMENT GOALS PADA PROGRAM DESA BERDAYA - TAMAN INSPIRASI WAIBU - Landi Simanjuntak; Linus Sandi Satya; M. Calvin Braggi; Komunitas Kitorang (Jurnal Ekonomika: Manajemen, Akuntansi, dan Perbankan Syari'ah, 2024)
This research explores the implementation of Sustainable Development Goals (SDGs) through the Penta-Helix collaboration in the Empowered Village Program - Waibu Inspiration Park. This research specifically focuses on the Penta-Helix Collaboration Analysis in SDGs Implementation efforts, especially in the context of the Empowered Village Program - Waibu Inspiration Park. The research uses descriptive qualitative methods, combining field and library research. The research results show that this cross-sector collaboration is effective in achieving sustainable development goals, especially at the village level. The success of this program illustrates the potential of the Penta-Helix collaborative model as a solution to global challenges. This abstract summarizes the research methodology and main findings, providing in-depth insights into the dynamics of collaboration and the impact of SDGs implementation at the village level.